Pharmacokinetics of darunavir/cobicistat and etravirine alone and co-administered in HIV-infected patients. (11th December 2017) - Moltó, José; Curran, Adrian; Miranda, Cristina; Challenger, Elizabeth; Santos, José Ramón; Ribera, Esteban; Khoo, Saye; Valle, Marta; Clotet, Bonaventura
Abstract: Objectives: To determine the effect of etravirine on the pharmacokinetics of darunavir/cobicistat and vice versa. Safety and tolerability of this combination were also evaluated. Methods: Open-label, fixed-sequence trial in two cohorts of HIV-infected patients on therapy with darunavir/cobicistat 800/150 mg once daily (DRV cohort; n = 15) or etravirine 400 mg once daily (ETR cohort; n = 15). Etravirine or darunavir/cobicistat were added on days 1–14 and 1–7 in participants in the DRV or ETR cohort, respectively. Full pharmacokinetic profiles were obtained on days 0 and 14 in the DRV cohort, and on days 0 and 7 in the ETR cohort. Darunavir, cobicistat and etravirine pharmacokinetic parameters [AUC0–24, C max and trough concentrations in plasma ( C 24 )] were calculated for each individual by non-compartmental analysis and were compared using linear mixed-effects models. Adverse events and HIV-1 RNA in plasma were monitored. Results: Etravirine co-administration decreased cobicistat AUC0–24, C max and C 24 by 30%, 14% and 66%, respectively. Although darunavir AUC0–24 and C max were unchanged by etravirine, darunavir C 24 was 56% lower for darunavir/cobicistat co-administered with etravirine relative to darunavir/cobicistat alone. Etravirine pharmacokinetics were unchanged by darunavir/cobicistat. Treatments were well tolerated, and HIV-1 RNA remained undetectable in all participants. Conclusions: Although etravirine pharmacokinetics was unchanged by darunavir/cobicistat, there was a significant decrease in cobicistat exposure and in darunavir C 24 when darunavir/cobicistat was co-administered with etravirine. Boosting darunavir with ritonavir instead of with cobicistat may be preferred if darunavir is to be combined with etravirine in clinical practice.